The psychological impact of COVID-19 on antenatal women: a scoping review - Mohd Arifin, Siti Roshaidai; Hassan, Noor Artika (IIUM Press, 2020)
The widespread transmission of the new coronavirus disease COVID-19 has caused great psychological distress across diverse populations in many countries. Antenatal women are at greater risk of emotional instability and vulnerability due to hormonal changes, and multiple maternal roles. This paper aims to determine the common types of psychological distress and potential interventions amongst antenatal women during COVID-19 outbreak. This review was conducted as a rapid review in response to the COVID-19 outbreak. The PubMed, Scopus, and Google Scholar databases were searched using keywords namely “novel coronavirus”, “COVID-19”, “nCoV”, “maternal mental health”, “pregnant”, “psychology”, “anxiety”, “depression” and “stress” in various permutations and combinations. A total of five papers were included in the final analysis. Thematic analysis was used to analyse the selected papers. Findings from the papers reviewed showed that COVID-19 has independently increased the prevalence of psychological distress among antenatal mothers. The most common types of distress were anxiety (57%- 83.3%), followed by worry (50.7%) and depression (34.2-37%). The distress experienced by the antenatal women with COVID-19 was found to be associated with suicidal thought. Social support, psychological hotlines, and online counselling have been suggested to alleviate the symptoms of mental distress among antenatal women. The COVID-19 pandemic has independently caused psychological distress among antenatal women to rise. Maternal mental health should be prioritised during the pandemic, and mental support should be made available and accessible during and after the COVID-19 outbreak in ensuring the ongoing provision of mental health services.